RISK MANAGEMENT IN RESEARCH AND DEVELOPMENT (R&D) PROJECTS: THE CASE OF SOUTH AUSTRALIA - Ricky Luppino; M. Reza Hosseini; Raufdeen Rameezdeen (Asian Academy of Management Journal, 2014)
A definition of the effective methods of risk management in R&D projects has remained elusive. Similarly, there have been calls to devise effective risk management methods in R&D projects. To develop this area further, the purpose of this study is twofold. First, it validates the veracity of claims about the urgency of introducing effective methods of risk management to R&D projects in South Australia based on nine unstructured interviews with experts. Second, the study presents the outcomes of two case studies that deployed the extended version of the failure mode and effect analysis, namely, the RFMEA method in a South Australian organisation, to investigate how the method can facilitate the identification of effective contingency plans to mitigate high-priority risks. The findings showed that the RFMEA method would be effective for project managers in dealing with risk management issues in R&D projects. The discussions presented will provide guidelines for practitioners in the industry.